Pastoral Subjugation in Hannah Kent’s Burial Rites: A Biopolitical Outlook - Sharma, Pradeep (Literary Studies, 2021)
Hannah Kent’s Burial Rites (2013) reflects the bare life of its protagonist, Agnes. She leads her Muselmann life from her outset of life. Grown up as foster child, she works as a farm maid whose rightful position is entirely ignored and eventually she is condemned to death. Natan molests her and she is banished from his home at night during snow fall when she demands her legal status at his home. Later she is accused of killing Natan and his friend. Before her execution, in order to tame and domesticate her, a priest is deployed who uses pastoral power, part of biopolitics that executes power over body. She unbuttons her pathetic life history along with her penitence. Finally, she leads a life of ‘homo sacer’ bearing the injustices like the superstes of holocaust and succumbed to condemnation.